Pengaruh Pembelajaran Al-Miftah lil-Ulum Terhadap Kemampuan Membaca dan Memahami Kitab Fathul Qarib Santri Pondok Pesantren - Zahid, Ahmad; Khoiruddin, Khoiruddin; Mahrus, Erwin; Usman, Usman (Sekolah Tinggi Agama Islam Sumatera Medan, 2024)
The ability to read turast is urgent for boarding school students, it becomes a tool for studying all learning studies in boarding schools. The purpose of this study was to determine the effect of Al-Miftah Lil-Ulum on the ability to read the yellow book of Fathul Qarib. the research method used is quantitative, while the data collection technique uses a test instrument in the form of multiple choice that has been tested through the Aiken V test with 3 expert lecturers as assessors then and the person correlation validity test and the reliability test. While the analysis test used is Path Analysis. The results of this research are that there is a direct influence of Al-Miftah Lil-Ulum learning variables on the ability to read the book of Fathul Qarib with a significance value of 0.011, there is a direct influence on the ability to read the book of Fathul Qarib on the ability to understand the book of Fathul Qarib with a significance level of 0, 000, there is a direct effect of Al-Miftah Lil-Ulum learning on the ability to understand the book of Fathul Qarib with a significance level of 0.000 and there is an indirect effect between Al-Miftah Lil-Ulum learning on the ability to understand the book of Fathul Qarib mediated by reading ability. This research has implications for evaluation to improve the ability of students to read the book of turast.